A high molecular weight polyethylene oxide, its method of preparation and use in oil fields

CN122978415APending Publication Date: 2026-10-27SHANGHAI LIANSHENG CHEM CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611146126.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,现有油田用PEO在实际应用中仍存在分子量分布不易控制、低分子量组分影响增粘效率、高分子量过宽组分易造成溶解分散不均等问题

Benefits of technology

[0014]由于采用以上技术方案,本发明的有益效果包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978415A_ABST
    Figure CN122978415A_ABST
Patent Text Reader

Abstract

The application discloses high-molecular-weight polyethylene oxide and a preparation method and application thereof in oil fields, and belongs to the technical field of polyethylene oxide. The preparation method of the high-molecular-weight polyethylene oxide comprises the following steps: adding anhydrous n-heptane and a catalyst into a reaction kettle and stirring and uniformly mixing; continuously adding first-stage ethylene oxide to perform first-stage reaction, and then continuously adding second-stage ethylene oxide to perform second-stage reaction; and obtaining the high-molecular-weight polyethylene oxide through post-treatment. The polyethylene oxide prepared by the application has high number average molecular weight, narrow molecular weight distribution and high polyethylene oxide yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyethylene oxide technology, specifically to a high molecular weight polyethylene oxide, its preparation method, and its application in oil fields. Background Technology

[0002] Polyethylene oxide (PEO) is a water-soluble nonionic polymer with excellent thickening, drag-reducing, lubricating, and film-forming properties, making it widely used in oilfield operation systems such as completion fluids, drilling fluids, oil displacement fluids, well maintenance fluids, and pipeline drag reduction. Especially in foam drilling fluids and polymer flooding systems, high molecular weight PEO can improve fluid viscoelasticity, rock-carrying capacity, and system stability, and helps reduce drill string friction, control filtration loss, and improve displacement effects. However, existing oilfield PEO applications still face challenges such as difficulty in controlling molecular weight distribution, low molecular weight components affecting thickening efficiency, and high molecular weight components causing uneven dissolution and dispersion. Currently, the catalytic systems for preparing high molecular weight PEO mainly include calcium ammonium catalytic systems, metal oxide supported catalytic systems, organoaluminum systems, and alkali metal alkoxide systems. While these systems can achieve ring-opening polymerization of ethylene oxide, some systems suffer from high process safety requirements, uneven dispersion of active centers, difficulty in controlling chain transfer side reactions, and a wide molecular weight distribution of the resulting PEO. Therefore, it is necessary to develop a new catalyst system and polymerization preparation method to enable ethylene oxide to polymerize stably on relatively uniform active centers, thereby preparing polyethylene oxide with higher molecular weight and narrower molecular weight distribution to meet different application scenarios such as oilfield drilling, oil displacement, oil well maintenance and pipeline drag reduction. Summary of the Invention

[0003] To address the shortcomings of existing technologies, the purpose of this invention is to provide a high molecular weight polyethylene oxide, its preparation method, and its application in oil fields.

[0004] A method for preparing high molecular weight polyethylene oxide includes the following steps: adding anhydrous n-heptane and a catalyst to a reaction vessel and stirring to mix; continuously adding first-stage ethylene oxide to carry out a first-stage reaction, and then continuously adding second-stage ethylene oxide to carry out a second-stage reaction, and obtaining high molecular weight polyethylene oxide after post-treatment; The catalyst is prepared by the following method: S1: Deionized water and magnesium aluminum hydrotalcite are stirred and mixed, and ammonium dihydrogen phosphate aqueous solution is added to react. After filtration, washing, drying, crushing, sieving and calcination, phosphate-anchored magnesium aluminum composite oxide carrier is obtained. S2: Anhydrous isopropanol and phosphate-anchored magnesium-aluminum composite oxide carrier are stirred and mixed, calcium oxide is added, the mixture is heated and stirred, anhydrous isopropanol solution containing glycerol and boric acid is added, the mixture is heated and reacted, and then obtained after rotary evaporation, drying and activation.

[0005] The mass ratio of the catalyst, the first-stage ethylene oxide, and the second-stage ethylene oxide is (0.007-0.013):2:1.

[0006] The temperature of the first stage reaction is 20-30℃, the time is 0.5-1.5h, and the gauge pressure is 0.2-0.3MPa.

[0007] The second stage reaction is carried out at a temperature of 35-42℃ for 1-2 hours and at a gauge pressure of 0.25-0.35 MPa.

[0008] In step S1, the mass ratio of magnesium aluminum hydrotalcite to ammonium dihydrogen phosphate is 1:(0.07-0.08); in step S2, the mass ratio of phosphate-anchored magnesium aluminum composite oxide carrier, calcium oxide, boric acid, and glycerol is 1:(0.075-0.1):(0.015-0.025):(0.08-0.09).

[0009] In step S1, the reaction temperature is 60-70℃ and the time is 1.5-2.5h; in step S2, the temperature for heating and stirring is 55-65℃ and the time is 35-45min; in step S2, the temperature for heating and reaction is 65-75℃ and the time is 3.5-4.5h.

[0010] In step S1, the calcination procedure is as follows: the temperature is increased to 480-520℃ at a heating rate of 1-2℃ / min, and then calcined for 2.5-3.5h.

[0011] In step S2, the activation procedure is as follows: heat to 180-200℃ at a heating rate of 1-2℃ / min, and hold for 2.5-3.5h.

[0012] A high molecular weight polyethylene oxide is prepared by the above-described preparation method.

[0013] Application of high molecular weight polyethylene oxide prepared by the above preparation method in oil fields.

[0014] Due to the adoption of the above technical solutions, the beneficial effects of the present invention include: In the catalyst preparation process, this application first modifies magnesium-aluminum hydrotalcite with ammonium dihydrogen phosphate for phosphoric acid anchoring, and then calcines it to form a phosphoric acid-anchored magnesium-aluminum composite oxide support. Then, calcium oxide, boric acid, and glycerol form a calcium-boron-glycerol alkoxide composite active structure on the support surface. The PO-Mg and PO-Al anchoring sites on the support surface can fix and confine the calcium active component, reducing the migration, aggregation, and local over-reaction of calcium species during polymerization. This results in uniformly dispersed polymerization active centers with moderate activity on the catalyst surface. The calcium alkoxide sites serve as the main initiation and chain growth centers for the ring-opening polymerization of ethylene oxide, while the borate sites can weakly coordinate and activate the ether oxygen in ethylene oxide. The polyhydroxy structure of glycerol enhances the multi-point coordination stabilization between calcium, boron, and the support, thereby enabling stable ring-opening growth of ethylene oxide on relatively uniform active centers, reducing chain transfer, chain termination, and the formation of low-molecular-weight byproducts. The stable interfacial anchoring structure also slows down the migration and deactivation of active components, allowing the catalyst to maintain high activity in the later stages of polymerization, thus improving the yield of polyethylene oxide. This application employs a two-stage, continuous addition of ethylene oxide during polymerization. In the first stage, the majority of the ethylene oxide is added at a lower temperature, gradually activating the catalyst's active centers and forming stable growing chains. This avoids uncontrolled chain growth caused by excessively high monomer concentrations and concentrated exothermic polymerization. In the second stage, the remaining ethylene oxide is added after a moderate temperature increase, allowing the already formed active chains to continue growing uniformly and promoting the full conversion of residual monomers. Continuous feeding and staged temperature control also reduce the loss of unreacted ethylene oxide, oligomers, and byproducts during post-processing, thereby improving the polyethylene oxide yield. Furthermore, by adjusting the amount of catalyst used in this application, the number of effective active centers and the ratio of ethylene oxide to active centers can be changed, enabling the controllable preparation of polyethylene oxide with different number-average molecular weights to meet the differentiated requirements of various application systems for viscosity enhancement, drag reduction, and rheological properties. Therefore, the polyethylene oxide prepared in this application has a high number-average molecular weight, a narrow molecular weight distribution, and a high yield. Moreover, it has controllable reaction properties, which is beneficial to improving its viscosity-enhancing, viscoelasticity, and stability in oilfield drilling fluids, oil displacement fluids, and pipeline drag reduction systems. Attached Figure Description

[0015] Figure 1 A scanning electron microscope image of the catalyst prepared in Example 2; Figure 2 The infrared spectrum of the catalyst prepared in Example 2; Figure 3 X-ray diffraction pattern of the catalyst prepared in Example 2; Figure 4 The X-ray photoelectron spectroscopy (XPS) spectrum of the catalyst prepared in Example 2; Figure 5 This is a graph showing the relationship between different catalyst dosages and the number-average molecular weight and molecular weight distribution of polyethylene oxide. Detailed Implementation

[0016] Example 1: Preparation of Catalyst S1: Mix 500ml of deionized water and 100g of magnesium aluminum hydrotalcite, stir at 25℃ and 500rpm for 30min, add 100ml of deionized water containing 7g of ammonium dihydrogen phosphate dropwise (adjust pH to 8.8±0.2 with 10wt% ammonia water during the dropwise addition), and after the 30min addition is complete, raise the temperature to 60℃ and stir at 500rpm for 2.5h; filter, wash the filter cake with deionized water until the conductivity of the filtrate is 50μS / cm, dry in a 105℃ forced-air drying oven for 8h, pulverize and pass through a 100-mesh sieve; place in a tube furnace, heat to 480℃ at a heating rate of 1℃ / min under air atmosphere, hold at the temperature for 3.5h, cool to room temperature with the furnace to obtain the phosphate-anchored magnesium aluminum composite oxide carrier; S2: Under nitrogen protection, 350 ml of anhydrous isopropanol and 80 g of phosphate-anchored magnesium aluminum composite oxide support were mixed and stirred at 25 °C and 500 rpm for 30 min. 6 g of calcium oxide was added, the temperature was raised to 55 °C and stirring was continued for 45 min. 50 ml of anhydrous isopropanol solution containing 6.4 g of glycerol and 1.2 g of boric acid was added dropwise over 40 min. The temperature was raised to 65 °C and stirring was continued for 4.5 h. The mixture was then rotary evaporated at 50 °C for 1 h. It was first vacuum dried at 80 °C and -0.09 MPa for 2 h, and then vacuum dried at 120 °C for 4 h. The mixture was placed in a tube furnace and heated to 180 °C at a rate of 1 °C / min under dry nitrogen (nitrogen flow rate of 250 ml / min). It was held at this temperature for 3.5 h for activation and then cooled to room temperature with the furnace under dry nitrogen protection to obtain the catalyst.

[0017] Example 2 Preparation of Catalyst S1: Mix 500ml deionized water and 100g magnesium aluminum hydrotalcite, stir at 25℃ and 500rpm for 30min, then add 100ml of deionized water containing 7.5g ammonium dihydrogen phosphate dropwise (adjust pH to 8.8±0.2 with 10wt% ammonia water during the addition). After the addition is complete in 30min, raise the temperature to 65℃ and stir at 500rpm for 2h. Filter, wash the filter cake with deionized water until the conductivity of the filtrate is 50μS / cm, and dry in a 105℃ forced-air drying oven for 8 hours. h, after being crushed, it is passed through a 100-mesh sieve; placed in a tube furnace, heated to 500℃ at a heating rate of 2℃ / min under air atmosphere, held at the temperature for 3h, and cooled to room temperature with the furnace to obtain a phosphate-anchored magnesium-aluminum composite oxide carrier; during the reaction process, phosphate ions adsorb, coordinate and anion exchange with Mg-OH and Al-OH sites on the surface of magnesium-aluminum hydrotalcite. After calcination, magnesium-aluminum hydrotalcite is dehydrated and dehydroxylated to transform into magnesium-aluminum composite oxide, while phosphate ions form PO-Mg and PO-Al structures with Mg and Al.

[0018] S2: Under nitrogen protection, 350 ml of anhydrous isopropanol and 80 g of phosphate-anchored magnesium-aluminum composite oxide support were mixed and stirred at 25 °C and 500 rpm for 30 min. 7 g of calcium oxide was added, and the mixture was heated to 60 °C and stirred for another 40 min. 50 ml of anhydrous isopropanol solution containing 6.8 g of glycerol and 1.6 g of boric acid was added dropwise over 40 min. The mixture was then heated to 70 °C and stirred for another 4 h. The mixture was then rotary evaporated at 50 °C for 1 h. It was first vacuum dried at 80 °C and -0.09 MPa for 2 h, then heated to 120 °C and vacuum dried for another 4 h. The mixture was then placed in a tube furnace and dried under dry conditions. Under dry nitrogen (nitrogen flow rate of 250 ml / min), the temperature was increased to 190℃ at a heating rate of 2℃ / min, and activated at this temperature for 3 h. The catalyst was then cooled to room temperature in the furnace under dry nitrogen protection to obtain the catalyst. During this reaction, calcium oxide and the phosphate anchoring sites and hydroxyl groups on the surface of the phosphate-anchored magnesium-aluminum composite oxide support undergo interfacial bonding. Glyceryl hydroxyl groups undergo coordination and alkoxide reactions with calcium species, and boric acid undergoes complexation and partial dehydration condensation with glyceryl hydroxyl groups, thereby forming calcium alkoxide, boron-oxygen structure and calcium-boron glycerol alkoxide composite active structure on the surface of the phosphate-anchored magnesium-aluminum composite oxide support.

[0019] Figure 1 The image shows a scanning electron microscope image of the catalyst. As can be seen from the image, the catalyst has an irregular particulate morphology. The particles are stacked together to form a lot of pores and a rough surface structure. Fine particles and flocculent structures can be observed attached to the particle surface.

[0020] Figure 2 The image shows the infrared spectrum of the catalyst. As can be seen from the figure, at 3445 cm⁻¹... -1 The relatively broad absorption peaks appearing nearby mainly correspond to the stretching vibrations of hydroxyl groups and a small amount of adsorbed water (OH); at 2926 cm⁻¹-1 and 2856cm -1 The presence of a CH stretching vibration absorption peak nearby indicates that the catalyst retains glycerol-related organic structures; at 1235 cm⁻¹... -1 1122cm -1 1078cm -1 and 1034cm -1 The absorption peaks appearing nearby are mainly attributed to the superposition of absorptions from the stretching vibrations of phosphate (PO), boron-oxygen structures (BO), and CO; at 958 cm⁻¹ -1 The nearby absorption peaks may be related to phosphate, boron-oxygen structures, and metal-oxygen-phosphorus interface vibrations; in the 782-520 cm⁻¹ range... -1 The absorption peaks observed within the range are mainly related to the bending vibrations of Mg-O, Al-O, Ca-O, and phosphate. The above infrared results indicate that the catalyst contains magnesium-aluminum composite oxides, phosphate, boron-oxygen structures, and glycerol-related organic structures.

[0021] Figure 3 The X-ray diffraction (XRD) pattern of the catalyst shows that broad, diffuse peaks and weak shoulders appear in the diffraction angle range of approximately 20°–32°, indicating the presence of a certain amount of low-crystalline or amorphous components in the catalyst. More pronounced diffraction peaks appear near diffraction angles of 36.8°, 43.0°, and 62.4°, while weak or broad diffraction peaks appear near 54°, 67°, and 75°–78°, mainly corresponding to the MgO-like magnesium-aluminum composite oxide crystal phase formed after calcination of magnesium-aluminum hydrotalcite. Some of these peaks may overlap with the diffraction peaks of small-grained or low-crystalline CaO-related species. The XRD results combined with infrared analysis further demonstrate that calcium, boron, phosphorus, and glycerol-related components are loaded onto the surface of the magnesium-aluminum composite oxide support.

[0022] Figure 4The image shows the X-ray photoelectron spectroscopy (XPS) spectrum of the catalyst. As can be seen, characteristic signal peaks for Mg 1s, O 1s, Ca 2p, C 1s, B 1s, P 2p, Al 2p, and Mg 2p appear near binding energies of approximately 1304.2 eV, 531.2 eV, 347.2 eV, 285.2 eV, 192.3 eV, 133.5 eV, 74.3 eV, and 50.5 eV, respectively. This indicates that the catalyst contains Mg, Al, O, Ca, P, B, and C elements. Among these, Mg, Al, and O elements originate from the magnesium-aluminum composite oxide support formed by calcination of magnesium-aluminum hydrotalcite; P element originates from the surface phosphate structure formed by ammonium dihydrogen phosphate modification; Ca and B elements originate from the supported calcium oxide and boric acid-related components, respectively; and C element is mainly related to the glycerol-related structures retained on the catalyst surface and a small amount of adsorbed carbon. No obvious characteristic peaks of other impurity elements were observed in the spectrum, indicating that the calcium, boron, phosphorus and carbon-containing components introduced during the preparation process can be retained on the surface of the magnesium-aluminum composite oxide carrier.

[0023] Example 3 Preparation of Catalyst S1: Mix 500ml of deionized water and 100g of magnesium aluminum hydrotalcite, stir at 25℃ and 500rpm for 30min, add 100ml of deionized water containing 8g of ammonium dihydrogen phosphate dropwise (adjust pH to 8.8±0.2 with 10wt% ammonia water during the dropwise addition), and after the dropwise addition is completed in 30min, raise the temperature to 70℃ and stir at 500rpm for 1.5h; filter, wash the filter cake with deionized water until the conductivity of the filtrate is 50μS / cm, dry in a 105℃ forced-air drying oven for 8h, pulverize and pass through a 100-mesh sieve; place in a tube furnace, heat to 520℃ at a heating rate of 2℃ / min under air atmosphere, hold at the temperature for 2.5h, cool to room temperature with the furnace to obtain the phosphate-anchored magnesium aluminum composite oxide carrier; S2: Under nitrogen protection, 350 ml of anhydrous isopropanol and 80 g of phosphate-anchored magnesium-aluminum composite oxide support were mixed and stirred at 25 °C and 500 rpm for 30 min. 8 g of calcium oxide was added, the temperature was raised to 65 °C and stirring was continued for 35 min. 50 ml of anhydrous isopropanol solution containing 7.2 g of glycerol and 2 g of boric acid was added dropwise over 40 min. The temperature was raised to 75 °C and stirring was continued for 3.5 h. The mixture was then rotary evaporated at 50 °C for 1 h. It was first vacuum dried at 80 °C and -0.09 MPa for 2 h, and then vacuum dried at 120 °C for 4 h. The mixture was placed in a tube furnace and heated to 200 °C at a rate of 2 °C / min under dry nitrogen (nitrogen flow rate of 250 ml / min). It was held at this temperature for 2.5 h for activation and then cooled to room temperature with the furnace under dry nitrogen protection to obtain the catalyst.

[0024] Example 4 Preparation of high molecular weight polyethylene oxide The reactor was vacuum-dried at 90℃ and a gauge pressure of -0.095 MPa for 3 hours. After cooling to room temperature, it was purged with nitrogen three times. Under nitrogen protection, 2000 ml of anhydrous n-heptane and 2.8 g of catalyst (prepared in Example 1) were added to the reactor, and the mixture was stirred at 25℃ and 350 rpm for 20 minutes. The reactor temperature was controlled at 20℃ and the gauge pressure at 0.2 MPa. 700 g of ethylene oxide was continuously added over 3.5 hours (the addition rate of ethylene oxide was adjusted according to the temperature and pressure changes during the addition process to maintain the reaction temperature at 20℃ and the gauge pressure at 0.2 MPa). After the addition was complete, the reactor was kept at 20℃ for another 1.5 hours. Subsequently, the temperature was increased to 35℃ at a rate of 0.2℃ / min, and the gauge pressure of the reactor was controlled at 0.2 MPa. 5 MPa, continue to add 350 g of ethylene oxide over 2.5 h (adjust the ethylene oxide addition rate according to the temperature and pressure changes in the reactor during the addition process to maintain the reaction temperature at 35℃ and the gauge pressure at 0.25 MPa). After addition, continue to keep the reaction at 35℃ for 2 h. Cool down to 15℃ and slowly release unreacted ethylene oxide into the tail gas absorption system. The tail gas absorption liquid is a 5 wt% dilute sulfuric acid aqueous solution. After the reactor pressure returns to atmospheric pressure, introduce carbon dioxide until the gauge pressure reaches 0.05 MPa and maintain for 20 min. Add 150 ml of anhydrous ethanol and stir at 350 rpm for 30 min. Neutralize with 20 ml of 0.5 wt% acetic acid in anhydrous ethanol solution and filter to obtain the crude product. Wash the crude product sequentially with n-heptane (2 × 500 ml) and anhydrous ethanol (2 × 300 ml). Vacuum dry at 45℃ and -0.09 MPa for 12 h to obtain high molecular weight polyethylene oxide.

[0025] Example 5 Preparation of high molecular weight polyethylene oxide The reactor was vacuum-dried at 90℃ and a gauge pressure of -0.095 MPa for 3 hours. After cooling to room temperature, it was purged with nitrogen three times. Under nitrogen protection, 2000 ml of anhydrous n-heptane and 3 g of catalyst (prepared in Example 2) were added to the reactor, and stirred at 25℃ and 350 rpm for 20 minutes. The reactor temperature was controlled at 25℃ and the gauge pressure at 0.25 MPa. 700 g of ethylene oxide was continuously added over 3.5 hours (the addition rate of ethylene oxide was adjusted according to the temperature and pressure changes during the addition process to maintain the reaction temperature at 25℃ and the gauge pressure at 0.25 MPa). After the addition was complete, the reactor was kept at 25℃ for another hour. Subsequently, the temperature was increased to 38℃ at a rate of 0.2℃ / min, and the gauge pressure of the reactor was controlled at 0.3 MPa. Pa, continue to add 350g of ethylene oxide over 2.5h (adjust the ethylene oxide addition rate according to the temperature and pressure changes in the reactor during the addition process to maintain the reaction temperature at 38℃ and the gauge pressure at 0.3MPa). After the addition is complete, continue to keep the reaction at 38℃ for 1.5h. Cool down to 15℃ and slowly release unreacted ethylene oxide into the tail gas absorption system. The tail gas absorption liquid is a 5wt% dilute sulfuric acid aqueous solution. After the reactor pressure returns to normal, introduce carbon dioxide until the gauge pressure reaches 0.05MPa and maintain for 20min. Add 150ml of anhydrous ethanol and stir at 350rpm for 30min. Neutralize with 20ml of 0.5wt% acetic acid in anhydrous ethanol solution and filter to obtain the crude product. Wash the crude product sequentially with n-heptane (2×500ml) and anhydrous ethanol (2×300ml). Vacuum dry at 45℃ and -0.09MPa for 12h to obtain high molecular weight polyethylene oxide.

[0026] Example 6 Preparation of high molecular weight polyethylene oxide The reactor was vacuum-dried at 90℃ and a gauge pressure of -0.095 MPa for 3 hours. After cooling to room temperature, it was purged with nitrogen three times. Under nitrogen protection, 2000 ml of anhydrous n-heptane and 3.5 g of catalyst (prepared in Example 3) were added to the reactor, and stirred at 25℃ and 350 rpm for 20 minutes. The reactor temperature was controlled at 30℃ and the gauge pressure at 0.3 MPa. 700 g of ethylene oxide was continuously added over 3.5 hours (the addition rate of ethylene oxide was adjusted according to the temperature and pressure changes during the addition process to maintain the reaction temperature at 30℃ and the gauge pressure at 0.3 MPa). After the addition was complete, the reactor was kept at 30℃ for another 0.5 hours. Subsequently, the temperature was increased to 42℃ at a rate of 0.2℃ / min, and the gauge pressure of the reactor was controlled at 0.3 MPa. 5 MPa, continue to add 350 g of ethylene oxide over 2.5 h (adjust the ethylene oxide addition rate according to the temperature and pressure changes in the reactor during the addition process to maintain the reaction temperature at 42 °C and the gauge pressure at 0.35 MPa). After addition, continue to react at 42 °C for 1 h. Cool down to 15 °C and slowly release unreacted ethylene oxide into the tail gas absorption system. The tail gas absorption liquid is a 5 wt% dilute sulfuric acid aqueous solution. After the reactor pressure returns to atmospheric pressure, introduce carbon dioxide until the gauge pressure reaches 0.05 MPa and maintain for 20 min. Add 150 ml of anhydrous ethanol and stir at 350 rpm for 30 min. Neutralize with 20 ml of 0.5 wt% acetic acid in anhydrous ethanol solution and filter to obtain the crude product. Wash the crude product sequentially with n-heptane (2 × 500 ml) and anhydrous ethanol (2 × 300 ml). Vacuum dry at 45 °C and -0.09 MPa for 12 h to obtain high molecular weight polyethylene oxide.

[0027] Figure 5 The figure shows the relationship between different catalyst dosages and the number-average molecular weight and molecular weight distribution of polyethylene oxide. The preparation method of polyethylene oxide is basically the same as in Example 5, except for the amount of catalyst used. As can be seen from the figure, with the increase of catalyst dosage, the number-average molecular weight of the prepared polyethylene oxide first increases and then gradually decreases. Furthermore, by adjusting the amount of catalyst used in this application, it is possible to control the number-average molecular weight of polyethylene oxide to be between 1.2 million and 4 million, while simultaneously controlling the molecular weight distribution of the obtained polyethylene oxide between 1.04 and 1.11, resulting in a relatively narrow molecular weight distribution.

[0028] Comparative Example 1 The preparation method of high molecular weight polyethylene oxide is basically the same as that in Example 5, except that the catalyst is replaced with an equal weight of a catalyst prepared by the following method: The preparation method of the catalyst is basically the same as that in Example 2, except that 7.5g of ammonium dihydrogen phosphate in step S1 is replaced with 7.8g of anhydrous sodium dihydrogen phosphate.

[0029] Comparative Example 2 The preparation method of high molecular weight polyethylene oxide is basically the same as that in Example 5, except that the catalyst is replaced with an equal weight of a catalyst prepared by the following method: The preparation method of the catalyst is basically the same as that in Example 2, except that the amount of ammonium dihydrogen phosphate in step S1 is replaced with 10g.

[0030] Comparative Example 3 The preparation method of high molecular weight polyethylene oxide is basically the same as that in Example 5, except that the catalyst is replaced with an equal weight of a catalyst prepared by the following method: The preparation method of the catalyst is basically the same as that in Example 2, except that 7g of calcium oxide in step S2 is replaced with 9.25g of calcium hydroxide.

[0031] Comparative Example 4 The preparation method of high molecular weight polyethylene oxide is basically the same as that in Example 5, except that the catalyst is replaced with an equal weight of a catalyst prepared by the following method: The preparation method of the catalyst is basically the same as that in Example 2, except that 1.6g of boric acid in step S2 is replaced with 2.5g of borax decahydrate.

[0032] Comparative Example 5 The preparation method of high molecular weight polyethylene oxide is basically the same as that in Example 5, except that the catalyst is replaced with an equal weight of a catalyst prepared by the following method: The preparation method of the catalyst is basically the same as that in Example 2, except that 6.8g of glycerol in step S2 is replaced with 6.9g of ethylene glycol.

[0033] Comparative Example 6 The preparation method of high molecular weight polyethylene oxide is basically the same as that in Example 5, except that the catalyst is replaced with an equal weight of a catalyst prepared by the following method: The preparation method of the catalyst is basically the same as that in Example 2, except that 6.8g of glycerol in step S2 is replaced with 7.5g of pentaerythritol.

[0034] Comparative Example 7 The preparation method of high molecular weight polyethylene oxide is as follows: The reactor was vacuum dried at 90℃ and gauge pressure -0.095MPa for 3 hours. After cooling to room temperature, it was purged with nitrogen three times. Under nitrogen protection, 2000 ml of anhydrous n-heptane and 3 g of catalyst (prepared in Example 2) were added to the reactor. The mixture was stirred at 25°C and 350 rpm for 20 min. The reactor temperature was controlled at 30°C and the gauge pressure at 0.28 MPa. 1050 g of ethylene oxide was continuously added over 6 h (the addition rate was adjusted according to the reactor temperature and pressure changes during the addition process to maintain the reaction temperature at 30°C and the gauge pressure at 0.28 MPa). After addition, the reaction was maintained at 30°C for another 2.5 h. The temperature was lowered to 15°C, and unreacted ethylene oxide was slowly released into the tail gas absorption system. The tail gas absorption liquid was a 5 wt% dilute sulfuric acid aqueous solution. After the reactor pressure returned to atmospheric pressure, carbon dioxide was introduced until the gauge pressure reached 0.05 MPa and maintained for 20 min. 150 ml of anhydrous ethanol was added, and the mixture was stirred at 350 rpm for 30 min. 20 ml of the solution was then used. Neutralize with an anhydrous ethanol solution of 0.5 wt% acetic acid, filter to obtain crude product; wash the crude product successively with n-heptane (2 × 500 ml) and anhydrous ethanol (2 × 300 ml), and vacuum dry at 45 °C and -0.09 MPa for 12 h to obtain high molecular weight polyethylene oxide.

[0035] The calcium oxide used in the catalyst preparation process of the embodiments and comparative examples of this application was calcined at 700°C for 2 hours before use, cooled, and stored under dry nitrogen protection; glycerol was vacuum dehydrated at 80°C and -0.09 MPa for 2 hours before use. The magnesium aluminum hydrotalcite was of type D205 and produced by Hefei Anyuhe New Material Technology Co., Ltd.; the ethylene oxide had a purity of 99.95% and a moisture content of 30 ppm.

[0036] The molecular weight and molecular weight distribution of the polyethylene oxide prepared in the examples and comparative examples were determined using a PLGPC50 gel chromatograph. The test results and the yield of polyethylene oxide are shown in Table 1.

[0037] Table 1 Performance Test Data Example 4 386 1.10 96.5 Example 5 418 1.04 97.4 Example 6 362 1.09 96.8 Comparative Example 1 325 1.03 93.6 Comparative Example 2 347 1.16 97.3 Comparative Example 3 306 1.27 93.7 Comparative Example 4 321 1.31 93.2 Comparative Example 5 364 1.06 94.0 Comparative Example 6 319 1.28 95.9 Comparative Example 7 340 1.07 95.1 As can be seen from the data in Table 1, the polyethylene oxide prepared in this application has a high number-average molecular weight, a narrow molecular weight distribution, and a high polyethylene oxide yield.

[0038] In Comparative Example 1, although anhydrous sodium dihydrogen phosphate can also provide phosphate ions, the residual sodium ions alter the acid-base environment of the carrier surface and the electronic state of the calcium active centers, reducing the chain growth ability of the calcium alkoxide sites. Therefore, the number-average molecular weight and yield decrease. In Comparative Example 2, increasing the amount of ammonium dihydrogen phosphate leads to excess phosphate easily covering the alkaline sites on the surface of the magnesium-aluminum composite oxide and potentially forming more inert calcium phosphate structures with the calcium source. This reduces the number and uniformity of effective active centers, resulting in a decrease in the molecular weight of polyethylene oxide and a wider molecular weight distribution.

[0039] In Comparative Example 3, calcium hydroxide contains a large number of hydroxyl groups and easily carries adsorbed water. It is difficult to completely eliminate the influence of water and hydroxyl groups during the activation process. In the process of ethylene oxide polymerization, chain transfer is easily triggered, which limits the growth of polymer chains. Therefore, the number average molecular weight decreases and the molecular weight distribution becomes wider. At the same time, some active centers are consumed or deactivated by water and hydroxyl groups, resulting in a decrease in the yield of polyethylene oxide.

[0040] In Comparative Example 4, the introduction of crystalline water and sodium ions by borax decahydrate affected the catalyst dehydration activation and the uniform formation of the Ca-OB synergistic structure, resulting in an unstable ethylene oxide ring-opening activation process, a decrease in the molecular weight of the obtained polyethylene oxide, a wider distribution, and a lower yield.

[0041] In Comparative Example 5, although ethylene glycol has a dihydroxy structure, its multi-site coordination ability is weaker than that of glycerol, making it difficult to form a stable three-dimensional coordination structure between calcium, boron, and the support. This leads to a decrease in the stability of the active center of the calcium-boron alkoxide, resulting in a decrease in the molecular weight and yield of polyethylene oxide. In Comparative Example 6, pentaerythritol has a large number of hydroxyl groups, but its dispersibility and reaction uniformity in anhydrous isopropanol are poor, and its steric hindrance is large, which is not conducive to the formation of a uniform and controllable active structure of calcium-boron polyhydroxy alkoxide. Therefore, the molecular weight of polyethylene oxide decreases, its distribution becomes wider, and its yield decreases.

[0042] Comparative Example 7 uses a single-stage continuous addition of all ethylene oxide. During the reaction, the monomer concentration and exothermic control are not as stable as in the two-stage process. This can easily cause some chain segments to grow prematurely, and some chain segments to be initiated or transferred later, resulting in a decrease in the synchronicity of chain growth. Therefore, the resulting polyethylene oxide has a lower molecular weight and a lower yield.

[0043] In the catalyst preparation process of this application, the conductivity of the filtrate of 50 μS / cm is an endpoint value for adjustment. In actual operation, as long as the conductivity is lower than or equal to 50 μS / cm, it is acceptable; it is not necessary to adjust it to this precise value of 50 μS / cm. Furthermore, the reaction temperature involved in this application needs to be controlled within ±2℃, and the post-treatment temperature needs to be controlled within ±3℃.

[0044] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. However, any modifications, alterations, and variations made by those skilled in the art without departing from the scope of the present invention based on the disclosed technical content are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing high molecular weight polyethylene oxide, characterized in that, Includes the following steps: Anhydrous n-heptane and catalyst were added to the reactor and stirred until homogeneous. First-stage ethylene oxide was continuously added to carry out the first-stage reaction, and then second-stage ethylene oxide was continuously added to carry out the second-stage reaction. After post-treatment, high molecular weight polyethylene oxide was obtained. The catalyst is prepared by the following method: S1: Deionized water and magnesium aluminum hydrotalcite are stirred and mixed, and ammonium dihydrogen phosphate aqueous solution is added to react. After filtration, washing, drying, crushing, sieving and calcination, phosphate-anchored magnesium aluminum composite oxide carrier is obtained. S2: Anhydrous isopropanol and phosphate-anchored magnesium-aluminum composite oxide carrier are stirred and mixed, calcium oxide is added, the mixture is heated and stirred, anhydrous isopropanol solution containing glycerol and boric acid is added, the mixture is heated and reacted, and then obtained after rotary evaporation, drying and activation.

2. The method for preparing high molecular weight polyethylene oxide according to claim 1, characterized in that, The mass ratio of the catalyst, the first-stage ethylene oxide, and the second-stage ethylene oxide is (0.007-0.013):2:

1.

3. The method for preparing high molecular weight polyethylene oxide according to claim 1, characterized in that, The temperature of the first stage reaction is 20-30℃, the time is 0.5-1.5h, and the gauge pressure is 0.2-0.3MPa.

4. The method for preparing high molecular weight polyethylene oxide according to claim 1, characterized in that, The second stage reaction is carried out at a temperature of 35-42℃ for 1-2 hours and at a gauge pressure of 0.25-0.35 MPa.

5. The method for preparing high molecular weight polyethylene oxide according to claim 1, characterized in that, In step S1, the mass ratio of magnesium aluminum hydrotalcite to ammonium dihydrogen phosphate is 1:(0.07-0.08); in step S2, the mass ratio of phosphate-anchored magnesium aluminum composite oxide carrier, calcium oxide, boric acid, and glycerol is 1:(0.075-0.1):(0.015-0.025):(0.08-0.09).

6. The method for preparing high molecular weight polyethylene oxide according to claim 1, characterized in that, In step S1, the reaction temperature is 60-70℃ and the time is 1.5-2.5h; in step S2, the temperature for heating and stirring is 55-65℃ and the time is 35-45min; in step S2, the temperature for heating and reaction is 65-75℃ and the time is 3.5-4.5h.

7. The method for preparing high molecular weight polyethylene oxide according to claim 1, characterized in that, In step S1, the calcination procedure is as follows: the temperature is increased to 480-520℃ at a heating rate of 1-2℃ / min, and then calcined for 2.5-3.5h.

8. The method for preparing high molecular weight polyethylene oxide according to claim 1, characterized in that, In step S2, the activation procedure is as follows: heat to 180-200℃ at a heating rate of 1-2℃ / min, and hold for 2.5-3.5h.

9. A high molecular weight polyethylene oxide, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.

10. The application of high molecular weight polyethylene oxide prepared by the preparation method according to any one of claims 1-8 in oil fields.